Photovoltaic System Performance Analysis with the Application of Hybrid Maximum Power Point Tracking Based on Incremental Conductance (INC) - Herawati, Afriyastuti; Oktavia, Sari; Satria Rinaldi, Reza; Rodiah, Yuli (Universitas Muhammadiyah Surakarta, 2025)
It requires work to maximize photovoltaic (PV) power output in order to maximize solar panel input to the battery and avoid overcharging or overdischarging. A technique to determine the value of the maximum power point (MPPT) is required in order to enhance the performance of photovoltaic systems and guarantee that solar panels run at the MPP. In the application of Standard Test Conditions (STC) in comparing the application without using MPPT, INC-based MPPT, and GWO-INC MPPT, it is found that to achieve the maximum power point of the panel, it is good to use the hybrid MPPT GWO-INC application, which gets the maximum power point tracking efficiency value of 64.34% and solar panel efficiency of 12.86% compared to without using MPPT which only gets the maximum power point tracking efficiency value of 52.9% with panel efficiency of 10.58%.